Meat and carcass traits of the red-winged tinamou (Rhynchotus rufescens) - de Queiroz, F. A. [UNESP]; de Carvalho, M. M.; Sugui, J. K. [UNESP]; Nunes, J. [UNESP]; Felipe, L. [UNESP]; dos Santos, E. C. [UNESP]; Tonhati, Humberto [UNESP]; Boiago, M. M.; Hata, M. E. [UNESP]; Tholon, P.; de Queiroz, S. A. [UNESP] (FapUNIFESP (SciELO), 2013)
Tinamou (Rhynchotus rufescens) is a native bird of the Brazilian fauna and has great potential to become a domesticated species. From this perspective, the objective of this study was to evaluate the carcass and main parts yield and to assess meat quality of that bird. Two trials, one studying stocking density and the other litter materials, lasting 60 days each, were conducted. The studied traits were evaluated in two birds/ replicate/treatment. Performance was evaluated by the least square method. The results showed that bird age at slaughter significantly influenced carcass and breast yields (p<0.05). Mean carcass, breast, thighs+drumstick and wing yields were 86.50±2.78%, 32.84±1.50%, 27.71±1.44%, and 13.21±0.94%, respectively. Shear force, pH, water holding capacity, lightness, redness and yellowness means and standard deviations were 1.92±0.98 kgf.cm-2, 6.07±0.12; 70±0.53%, 48.30±0.96, 1.96±1.01, and 1.61±1.0, respectively. Moisture, ash, crude protein, fat, and cholesterol contents were 72.35±0.16%, 1.12±0.06%, 25.53±0.50%, 0.17±0.01%, and 18.87±2.76 mg/10g, respectively. Results showed carcass and parts yields and the physicalchemical traits of tinamou meat are similar to chicken meat; however, tinamou meat is less acidic and has higher protein level combined with less calories and lower cholesterol levels.
Keywords: Carcass yield; Lightness; pH; Shear force; Water holding capacity